Cross-Dehydrogenative Coupling (CDC): Exploring C−C Bond Formations beyond Functional Group Transformations - Li, Chao-Jun (Accounts of chemical research, 2009)
Synthetic chemists aspire both to develop novel chemical reactions and to improve reaction conditions to maximize resource efficiency, energy efficiency, product selectivity, operational simplicity, and environmental health and safety. Carbon−carbon bond formation is a central part of many chemical syntheses, and innovations in these types of reactions will profoundly improve overall synthetic efficiency. This Account describes our work over the past several years to form carbon−carbon bonds directly from two different C−H bonds under oxidative conditions, cross-dehydrogenative coupling (CDC). We have focused most of our efforts on carbon−carbon bonds formed via the functionalization of sp3 C−H bonds with other C−H bonds. In the presence of simple and cheap catalysts such as copper and iron salts and oxidants such as hydrogen peroxide, dioxygen, tert-butylhydroperoxide, and 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ), we can directly functionalize various sp3 C−H bonds by other C−H bonds without requiring preactivation. We demonstrate (1) reaction of α-C−H bonds of nitrogen in amines, (2) reaction of α-C−H bonds of oxygen in ethers, (3) reaction of allylic and benzylic C−H bonds, and (4) reaction of alkane C−H bonds. These CDC reactions can tolerate a variety of functional groups, and some can occur under aqueous conditions. Depending on the specific transformation, we propose the in situ generation of different intermediates. These methods provide an alternative to the separate steps of prefunctionalization and defunctionalization that have traditionally been part of synthetic design. As a result, these methods will increase synthetic efficiencies at the most fundamental level. On an intellectual level, the development of C−C bond formations based on the reaction of only C−H bonds (possibly in water) challenges us to rethink some of the most fundamental concepts and theories regarding chemical reactivities. A successful reaction requires the conventionally and theoretically less reactive C−H bonds to react selectively in the presence of a variety of functional groups. With further investigation, we expect that C−C bond formations based on cross-dehydrogenative coupling will have a positive economic and ecological impact on the next generation of chemical syntheses.